PENGARUH PENERAPAN SAK BERBASIS IFRS TERHADAP FEE AUDIT PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI PADA TAHUN 2010 DAN 2013 - Afina Fauziyyah; Sudarno Sudarno (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of International Financial Reporting Standards (IFRS) adoption on audit fees in Indonesia. Client size, client complexity, and client risk used as control variable.The population in this study consists of manufactured listed firm in Indonesia Stock Exchange in year 2010 and 2013. Sampling method used is purposive sampling and used Ordinary Least Squares (OLS) cross-sectional regression as the analysis instrument. The final sample consists of data from a total of 116 financial statements representing 58 listed companies. The empirical result of this study show that members of international accounting firms (BIG4), client size, and client complexity have positively sifnificant influenced on audit fees. The adoption of IFRS has not significantly increased audit fees for Indonesian listed manufactured companies influenced on audit fees.